COMPARATIVE STUDY ON PHYSICAL EDUCATION LEARNING QUALITY OF JUNIOR HIGH SCHOOL STUDENTS UNDER DIFFERENT REARING MODES BASED ON ARTIFICIAL NEURAL NETWORK EXPERT SYSTEM - Yu Geng (Fonseca, Journal of Communication, 2024)
The purpose of this study is to evaluate the variations in bodily schooling mastering exceptional junior center college students underneath exceptional rearing modes and to use the specialist gadget primarily based on the synthetic neural community for analysis. The contrast index of gaining knowledge first-rate is an index gadget composed of numerous one-of-a-kind parameters. It is tough to be particular and has apparent fuzziness due to its giant variety and complicated content. There are many obstacles in fixing the contrast hassle using the skill of frequently used assessment methods. This paper proposes an assessment mannequin of junior excessive college students’ bodily schooling mastering excellent primarily based on a synthetic neural community specialist system. The purpose of this method is simply to put processed records in a community and generate results by computation, other than by manual computing. It decreases the number of people in the comparative procedure, enhances the credibility of the assessment, and makes the comparative result more enormous and objective. However, the neural community additionally has some limitations. It can obtain international optimization by continuously editing the connection weights between neurons; however, making the community fall into neighborhood minima is convenient.